The study of ISDN sales at Kedai Telekom Batu Lintang, Kuching/ Marini Omar - Omar, Marini (2002)
Telekom Sales and Services Sdn Bhd were incepted in 1989. As a wholly owned subsidiary of Telekom Malaysia, the country’s longest serving and premier telecommunications provider, TSSSB started off as part of a campaign to enhance customer service. Today, TSSSB has metamorphosized into one of the nation’s largest Telecommunications and IT retail chains, providing effective solutions for businesses as well as, an outstanding range of the latest telecommunication =s and IT products and services at home. ISDN, which stands for Integrated Services Digital Network, is a system of digital connections. This system serves as a multimedia platform allowing voice, data and traffic to be transmitted simultaneously using end-to-end digital connectivity. There are two basic types of ISDN service: Basic Rate Interface (BRI) and Primary Rate Interface (PRI).